Genotype selection and microbial partnerships influence chickpea establishment in lunar regolith simulant - Atkin, Jessica; Skabelund, Hikari; Pierson, Elizabeth; Zhen, Shuyang; Vandemark, George J.; Gentry, Terry (Frontiers in Astronomy and Space Sciences, 2025)
Sustainable food production is essential for long-duration Lunar missions, driving the development of in situ resource utilization strategies that use lunar regolith (LR) as a growth substrate for food crop cultivation. Although LR contains essential plant nutrients, it lacks organic matter and beneficial microbes. Its poor structure, low nitrogen content, and the presence of phytotoxic metals pose major challenges for plant germination, establishment, health, and successful fruit/seed production. On Earth, plant health and productivity are aided by microbial symbioses with mycorrhizal fungi, diazotrophic bacteria, and other rhizosphere colonizing organisms that facilitate nutrient availability, detoxify metals, and improve soil structure. This study evaluated 16 chickpea (Cicer arietinum) genotypes for seeding establishment, early plant development, and effective microbial symbiosis with rhizobia (Mesorhizobium ciceri) grown in vermicompost amended lunar regolith simulant (LRS) LHS-1. Chickpea is an ideal candidate for Lunar agriculture because it is a nutritionally dense food source and forms symbiotic relationships with arbuscular mycorrhizal fungi and rhizobia. Genotypes exhibited distinct growth strategies under LRS conditions, with considerable variation in total biomass production, differing by as much as 116 percent across genotypes, and in aboveground and belowground allocation. Notably, most genotypes showed strong nodulation with Mesorhizobium ciceri, suggesting potential for biological nitrogen fixation. These results inform breeding strategies for chickpea cultivars adapted to regolith-based systems and agriculture in challenging environments.